Zinc and Copper Levels Fluctuate with Altered Glucose Homeostasis - Nudrat Anwar Zuberi; Sabeela Noor; Fasiha Fatima; Khalilullah; Muhammad Iltaf (ziauddin University, 2024)
Background: Type 2 diabetes mellitus is becoming one of the major health problems worldwide. Especially in South East Asia, type 2 diabetes has gained critical significance. As pre-diabetes prevalence is increasing worldwide, it has become an important concern to prevent diabetes at an early stage. Trace elements have been gaining attention in improving the glucometabolic conditions like pre-diabetes and diabetes. Zinc and copper are the major trace elements present in the human body and they play a significant role in the pathogenesis of diabetes mellitus and pre-diabetes. Objectives: The purpose of this study was to compare serum zinc and copper levels in type 2 diabetes and pre-diabetes. Methods: This study was conducted in department of Biochemistry BMSI, JPMC Karachi. Total 90 subjects were taken out of which 30 were type 2 diabetics, 30 were pre-diabetics and 30 were normal healthy individuals. Serum fasting glucose was measured by glucose oxidase method. Serum zinc and copper were measured by colorimetric method. Statistical analysis was done using SPSS version 16. Results: Serum zinc levels were significantly lower in type 2 diabetics as compared to pre-diabetics and normal individuals (mean differences were 45.17±15.63µg/dl, 59.97±13µg/dl and 86.57±14.34 µg/dl respectively). Serum copper was significantly increased in type 2 diabetics compared to pre-diabetes and control samples (mean differences were 325.55±88.34 µg/dl, 175.53±47.45µg/dl and 126.87±21.57µg/dl respectively). Conclusion: It was concluded that serum zinc was significantly lower in type 2 diabetics and prediabetics and is inversely related to serum fasting glucose while serum copper is significantly higher and positively related with fasting blood glucose. KEY WORDS: Type 2 Diabetes, Pre-Diabetes, Zinc, Copper.